2020
DOI: 10.1038/s41419-020-2273-y
|View full text |Cite
|
Sign up to set email alerts
|

circRNA_0000140 suppresses oral squamous cell carcinoma growth and metastasis by targeting miR-31 to inhibit Hippo signaling pathway

Abstract: Oral squamous cell carcinoma (OSCC) is one of the most common malignancies and has a poor prognosis. Circular RNA (circRNA) has been increasingly recognized as a crucial contributor to carcinogenesis. circRNA_0000140 has been aberrantly expressed in OSCC, but its role in tumor growth and metastasis remains largely unclear. Sanger sequencing, actinomycin D, and RNase R treatments were used to confirm head-to-tail junction sequences and the stability of circ_0000140. In vitro cell activities, including prolifera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
105
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 154 publications
(114 citation statements)
references
References 36 publications
3
105
0
Order By: Relevance
“…In vivo experiments, we also proved that it could inhibit the tumor growth of OSCC. All data was similar with the results of Peng et al [14]. Further experiments showed that circ_0000140 could absorb miR-182-5p to regulate CDC73 expression.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…In vivo experiments, we also proved that it could inhibit the tumor growth of OSCC. All data was similar with the results of Peng et al [14]. Further experiments showed that circ_0000140 could absorb miR-182-5p to regulate CDC73 expression.…”
Section: Discussionsupporting
confidence: 91%
“…f, g The CDC73 protein level in CAL-27 and SCC-4 cells was detected by WB analysis to evaluate the circ_0000140 and miR-182-5p expression on CDC73 expression. ** P < 0.01 expression in OSCC patients [13,14]. We also discovered that circ_0000140 had a decreased expression in OSCC, and it was a stable cyclic transcript and mainly located in the cytoplasm.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…Once the Hippo pathway is inactivated, Yesassociated protein (YAP) and Tafazzin (TAZ) translocated into the nucleus to promote cell proliferation 60 . Numerous studies have also reported that the Hippo pathway participated in the progression of various malignancies 59,[61][62][63][64] .…”
Section: Discussionmentioning
confidence: 99%
“…Functionally, the expression of circ-0000140 can suppress cell proliferation, migration, and invasion, as well as facilitate cell apoptosis in vitro. Mechanistically, circ-0000140 enhances the expression of miR-31 and its target gene LATS2 by “sponging” miR-31, which suppresses the aggressive biological behavior of OSCC [ 30 ]. Su et al's study characterized hsa_circ_0005379 by using high-throughput transcriptome sequencing technology.…”
Section: Circular Rnas In Head and Neck Cancersmentioning
confidence: 99%